Pengaruh Metode Estafet Writing terhadap Keterampilan Menulis Siswa Kelas VIII SMP Negeri 2 Lubuk Sikaping - Intan Permata Sari; Andria Catri Tamsin; Ermawati Arief; Ena Noveria (Universitas Muhammadiyah Magelang, 2026)
This study aims to describe the short story writing skills of eighth grade students of SMP Negeri 2 Lubuk Sikaping before and after using the writing relay method, and to analyze the effect of the application of the writing relay method on students' short story writing skills. The approach used in this study is quantitative research with a pre-experimental research type. The research design used is one group pretest and posttest design consisting of one sample class. The sampling technique in this study is purposive sampling technique. The research data obtained are in the form of short story writing skill scores which are then converted into grades. The results of the study show that the short story writing skills of eighth grade students of SMP Negeri 2 Lubuk Sikaping after the application of the writing relay method have increased compared to before the treatment. The average value before the application of the writing relay method was at 69.60 with a qualification of More than Sufficient (LdC), while the average value after the treatment increased to 87.50 with a qualification of Very Good (BS). Based on the statistical test results, the calculated t value was greater than the t table (7.10>1.71) at a significance level of 0.05 and a 95% confidence level. Therefore, it can be concluded that the relay writing method significantly influenced students' short story writing skills.